Man and Future: a Palaeontological and Chronological Foundation of Cassirer's Definition of Man as Animal Symbolicum - Laino, Luigi (ETHICS IN PROGRESS, 2017)
In the present paper, the author aims at laying the foundations of a symbolics of technical gesture, according to the thesis that symbolic faculty is another face of the technological one, and that they are both in truth two sides of the same coin. Accordingly, the author suggests to rename the whole dimension as “meta-environmentality”. The analysis is carried out on the basis of a specific comparison between Cassirer’s definition of “animal symbolicum” and its scientific consistence in the light of modern palaeontology. “Animal symbolicum” is here compared with Leroi-Gourhan’s homo technologicus, and Cassirer’s ideas on human identity tested starting from paleoanthropological data. The result of the inquiry lead us to recognize the urgency of integrating Cassirer’s argument with the primacy of the technological capacity, but a deep analysis of the characterizing attributes of the latter compels us to uphold the symbolic attitude of the technological dimension. The author then sketches a basic description ofthe guidelines of a symbolic theory of technology (especially §§ 6-7), and tries to show how the basic elements of such an approach were familiar both to Cassirer and Leroi-Gourhan. As a consequence of the whole theory, the author elaborates a chronological analysis of human identity, whose basic result is the determination of the future as main temporal dimension of human acting.